Experimental investigation of ignition delay and laminar burning velocity of HVO/RP-3 blends as a drop-in aviation fuel under extended operating conditions - Linlin Gu; Xunkai Hu; Chongyang Liu; Dongdong Qi; JingYu Ran; Zhongqing Yang (Fuel, 2027)

hCG orchestrates ovulation in swamp eel (Monopterus albus) via progesterone, metabolic reprogramming, and pyroptosis - Mingsen Zhou; Linlin Wang; Shuo Zheng; Anfu Shen; Xuewen Rao; Liang Ke; Wenhao Hu; Changqing Han; Xiangjiang Liu; Guangfu Hu (Aquaculture, 2027)

Synthesis and characterization of porous carbon from Hawaii nut shells for effective CO2 capture - Xiaohan Liu; Yingyi Wang; Zhentao Chen; Xin Hu; Qiang Xiao; Leihong Zhao; Muslum Demir; Murat Kilic; Mohammed K. Al Mesfer; Linlin Wang (Biomass and Bioenergy, 2026)

MOF-derived carbon membranes for catalytic ozonation: Site-dependent evolution of surface atomic oxygen enables efficient water purification - Guanjin Liu; Linlin Zang; Dongwei Lu; Yinkun Sun; Hui Zhang; Yichao Hu; Zhiyu Sun; Wei Wang; Zhiqiang Sun; Jun Ma (Water Research, 2026)

Ultramicroporous N-doped carbons prepared by KHC2O4 activation for CO2 adsorption - Yujia Yin; Yingyi Wang; Ziyun Li; Ya Liu; Leihong Zhao; Muslum Demir; Aseel Zaid; Linlin Wang; Xin Hu (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China” [Food Res. Int. 242 (2026) 120014] - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Metagenomic insights into the distribution and potential influencing factors of antibiotic resistance genes in historically polluted lake sediments - Jinyang Fu; Zhunjie Li; Caixi Hu; Linlin Yao; Mengxi Cao; Yiran Dong; Pu Wang; Yong Liang; Lei Tong; Jianbo Shi (Aquatic Toxicology, 2026)

Biodegradable piezoelectric suture for real-time biomechanical sensing and therapeutic intervention - Quanhong Hu; Chuyu Tang; Zhirong Liu; Shaobo Wang; Zhuo Wang; Genglin Chen; Shuncheng Yao; Zhuoheng Jiang; Songjing Zhong; Yuxuan Zhang; Linlin Li (Science Bulletin, 2026)

Tea Rinsing Effectively Mitigates Probabilistic Health Risks From Heavy Metal Exposure - Shuangfei Hu; Linlin Jin; Lili Huang; Cuihong Liu; Minsi Liang; Hongtao Liu (Biological Trace Element Research, 2026)

Effects of the foliar application of selenite at different growth stages on selenium transformation, silage quality and the metabolome of tiger nut (Cyperus esculentus L.) - Kexin Wang; Ting Gong; Xinge Du; Wei Liu; Ruize Sun; Chenghao Che; Yilin Zou; Shengnan Sun; Linlin Mei; Guofu Hu (Food Chemistry, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Effects of combined selenium and sulfur application on glucosinolate biosynthesis in Chinese cabbage sprouts - Huixia Bai; Linlin Zhao; Yafang Luo; Qi Hu; Lingling Liu; Yang Chen; Huan Wang; Yushu Wang (Physiology and Molecular Biology of Plants, 2026)

Built-in electric field constructed by asymmetric electron cloud distribution for facilitating photocatalytic H2O2 production in covalent organic frameworks - Chuanxue You; Yue Zhou; Meiting Yang; Jingyang Li; Bo Hu; Yunchao Ma; Linlin Liu; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Characterization of a novel lytic Mooglevirus phage to control Salmonella Senftenberg and its application in foods - Jiayi Xue; Tingyu Liu; Linlin Xiao; Jiuchao Zhu; Yi Hong; Xiang Wang; Jinghang Zhang; Hengyi Hu; Zhuosi Li; Qingli Dong; Xiaojie Qin (Food Control, 2026)

Biochar and manure amendments mitigate chemical-fertilizer-induce negative effects on soil microbiomes, with implications for crop productivity gain - Pan Jiang; Hao Huang; Jinmeng Hu; Linlin Wang; Yuping Zhang; Xiangmin Rong; Jianwei Peng; Gongwen Luo (Applied Soil Ecology, 2026)

Unlocking the anatomical code of flavor and lipids in grass carp (Ctenopharyngodon idellus) fish oil from different tissue parts by SPME-GC–MS, molecular docking, and lipidomics - Huijuan Zhou; Linchuan Xu; Junru Bai; Linlin Weng; Chengwei Yu; Mingming Hu; Bizhen Zhong; Jinlin Li; Zongcai Tu; Bin Peng (Food Chemistry, 2026)

Chemical and sensory characteristics of Baiye No.1 (BY1H) yellow tea: Insights into flavoring mechanism and quality valuation - Shiyu Zhang; Xinzhuan Yao; Yanxia Wang; Muhammad Safiullah Virk; Shiyu Tian; Zhenkedai Yuan; Qihong Zou; Linlin Li; Shenyuan Ye; Hu Tang; Litang Lu (Food Bioscience, 2026)

Amyloid fibrillation of different ratios of 7S/11S soy protein: comparison of fibril structural characteristics and analysis of the potential for preparing high-internal-phase emulsions - Tianlu Han; Lidan Qiu; Qinlin Hu; Ruqi Guo; Ying Zhu; Yuyang Huang; LinLin Liu; Ying Wang; Xiuqing Zhu (Food Hydrocolloids, 2026)

A nanoengineered strategy combining deep oxygenation and immunogenicity regulation to unleash the power of anti-tumor immunity - Gang Cheng; Linlin Tao; Nian Huang; Xiaoxiao Hu; Mengmeng Yang; Fangnan Lv; Nan Yang; Siyuan Meng; Zuhang Xing; Boyu Gu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

Synergistic effects of crystal-facet on dehalogenation kinetics and poison tolerance of Pd-based electrocatalytic membranes for efficient removal of halogenated pollutants - Yinkun Sun; Dongwei Lu; Xianci Pan; Rongxin Zeng; Zhiyu Sun; Xueying Chen; Yumei Wang; Qingcan Zhou; Yichao Hu; Linlin Zang; Guanjin Liu; Jun Ma (Chemical Engineering Journal, 2026)

Holocene wildfire activity archived in East Asian marginal sea: Linkages to climate variability and human civilization - Linlin Chen; Yazhi Bai; Zhigang Guo; Weini Chong; Yuying Zhang; Jinming Bai; Yaru Liu; Haiyan Fang; Limin Hu (CATENA, 2026)

Black phosphorus with enhanced stability via palladium induced electronic structure modulation and its application in portable breath acetone sensing - Guangliang Li; Yunzhu Liu; Lei Ma; Hang Zhang; Jinlong Ma; Linlin Hou; Jian Duan; Guanglan Liao; Hu Long; Tielin Shi (Chemical Engineering Journal, 2026)

A machine learning-based model for aerosol scattering hygroscopic growth factor (f(RH)) prediction in Beijing urban area - Hongfei Tong; Xinyao Hu; Can Xia; Xiaojing Shen; Yangmei Zhang; Quan Liu; Lei Liu; Linlin Liang; Jiayuan Lu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2026)

Numerical Investigation of Wind-Wave Loads on Nuclear-Powered Icebreakers in Tornado Extreme Environments - Linlin Yin; Zhenju Chuang; Ankang Hu; Zhenze Yang; Jixu Yang (Journal of Marine Science and Engineering, 2025)
As critical assets for polar development and global strategy, nuclear-powered icebreakers necessitate rigorous safety research under extreme meteorological conditions. Evaluating their reliability under tornado loads is essential to ensure sustainable Arctic operations. This study employed numerical methods to solve tornado loads and assess the safety performance of an icebreaker subjected to tornado-induced loads. Tornado loads at varying azimuth angles were solved using a modified Ward-type simulator, while wave loads under tornado conditions were determined by a numerical wave model. The results demonstrated that the tornado applied the maximum wind load on the structure at a 0° azimuth angle. The total wind load was reduced by approximately 39% at a 60° azimuth angle. The tornado-induced moment on the ship exhibited a strongly nonlinear relationship with the azimuth angle. The maximum total moment occurred at a 15° azimuth angle, whereas the minimum total moment was observed at a 90° azimuth angle, where the hull experienced minimal wind loads.

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Remediation of alkaline cadmium (Cd) contaminated soil through biochar combined with organic fertilizer application - Linlin Liu; Jie Hu; Di Miao; Wenxin Yin; Wenping Sun; Lianglun Sun; Meizhen Tang (Environmental Geochemistry and Health, 2025)

How do atmospheric pollutant changes driven by anthropogenic heat provide feedback on the urban thermal environment in Beijing? - Jiangkang Qian; Linlin Zhang; Xinran Zhu; Qingyan Meng; Xinli Hu; Jianfeng Gao; Shize Chen (Sustainable Cities and Society, 2025)

Atmospheric and room temperature plasma mutagenesis of Graesiella emersonii for enhanced protein production using methanol as novel carbon source - Jixu Luo; Guanqin Huang; Mingjia Zheng; Changqing Ou; Qingyue Chen; Yufeng Ling; Linlin Cai; Yang Yang; Lingcheng Liu; Fei Huang; Zhangli Hu; Yihong Zheng (Bioresource Technology, 2025)

Atypical seasonal variability of the Kuroshio Current in 2018 - Fujun Wang; Linlin Zhang; Junqiao Feng; Qingye Wang; Dunxin Hu (Frontiers in Marine Science, 2025)
Introduction Using three moorings deployed at 122.7°E, 123°E, and 123.3°E along 18°N from January 2018 to May 2020, this study investigates the seasonal variability of the Kuroshio Current (KC). Methods Sensitive experiments were conducted with the Regional Ocean Modeling System (ROMS). Results In 2019, the KC exhibited a typical seasonal cycle, being relatively strong during spring, summer, and winter, with the weakest flow occurring in autumn. In contrast, the KC displayed an atypical seasonal cycle in 2018, characterized by two distinct intraseasonal intensification events in late September and early November. The ROMS experiments revealed that local winds within the region (120°E–125°E, 15°N–20°N) were the primary driver of this atypical cycle. During the two key periods, persistent negative wind stress curl anomalies east of the mooring stations induced integrated positive sea surface height anomalies and corresponding northward meridional velocity anomalies via geostrophic balance. Discussion In 2019, the wind stress curl anomaly phases reversed compared to 2018, leading to the absence of the two peaks observed in the previous year.

Proteomics and metabolic profiling of Vibrio parahaemolyticus at three different temperatures - Aiyun Meng; Zhigang Tu; Linlin Hu; Fuxiao Chen (Frontiers in Marine Science, 2025)
Introduction Microorganisms exist and survive in complex and variable environments. Bacteria communities response and adapt to the changing conditions. The Mechanisms underlying bacterial survival can be elucidated through the use of multi-omics techniques. Methods In this study, we test an approach for measuring how different temperatures (4°C, 25°C, and 37°C) affected bacterial physiological functions. Proteomic and metabolomic analyses were conducted on Vibrio parahaemolyticus LF1113 under different temperatures. Results and discussion A total of 2,899 proteins and 396 metabolites were identified. The differentially expressed proteins (DEPs) and differentially metabolites (DMs) were involved in Lysine degradation, metabolic pathways, ABC transporters, and microbial metabolism in diverse environments pathways. An integrated metabolomics/proteomics analysis approach was employed in this study. The analysis of both types of data information (proteins and metabolites) aids to reveal the microbial adaptive regulation in response to temperature stimuli. The study can further help clinical research of V. parahaemolyticus from the perspective of metabolomics and proteomics.

Amphiphilic Janus nanoparticles for effective foam fractionation of perfluorooctanoic acid (PFOA): Effect of modifier type - Yanfei Li; Zhuoxuan Zhang; Yanyan Lv; Yazhu Pei; Linlin Ding; Zhijun Zhang; Nan Hu (Environmental Research, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Characterization of TGFβ Signaling Components in Large Yellow Croaker (Larimichthys crocea) and Their Role in Growth and Body Shape Regulation - Xuyang Jiang; Lu Zhang; Xin Hu; Mingchao Cui; Jie Li; Huang Liu; Linlin Yao (Journal of Marine Science and Engineering, 2025)
The transforming growth factor β (TGFβ) signaling axis plays a pivotal role in orchestrating a wide array of biological functions, encompassing cellular growth, proliferation, and differentiation. The aim of the present study was to identify the members of TGFβ signaling pathway and their expression patterns in large yellow croaker (Larimichthys crocea) under different culture modes. TGFβ signaling pathway and their expression patterns in fish reared under two different culture modes: Group N (2400 fish in a 120 m3 cage) and Group V (168,000 fish in a 5600 m3 aquaculture vessel). After 120 days, we analyzed 15 fish from each group and found that Group V exhibited faster growth and a slender body shape compared to Group N. Bioinformatics analysis identified 48 TGFβ superfamily members in L. crocea, including 21 ligands, 10 receptors, and 3 Smads. mRNA expression levels indicated that these signaling molecules influence growth rate and body shape through five distinct ligand–receptor–R-Smad pathways, with the INHBB-, Nodal-, and GDF3-ACVR2A-ALK4-Smad2 axis playing a predominant role in regulating these traits.

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

An improved method for extracting cellulose from fossil wood and its paleoclimatic implications - Donghao Wu; Xin Wang; Yang Deng; Mi Wang; Gang Hu; Xuan Ding; Linlin Gao; Keyan Fang; Xiaohua Gou (Frontiers of Earth Science, 2025)

Dissolved organic matter sources in urban outfall water before and during rainfall, indicated via its fluorescence fingerprinting - Haojie Yin; Tao Huang; Bo Wang; Yingying Zhang; Jiawei Hu; Linlin Zhu; Kaining Chen (Applied Geochemistry, 2025)

Effect of cyanobacterial bloom proliferation on antibiotic resistance genes in the sediments of a eutrophic lake - Bo Wang; Tao Huang; Linlin Zhu; Jiawei Hu; Shaodong Ma; Qingye Sun; Kaining Chen (Environmental Research, 2025)

Dissolved organic matter (DOM) – Driven variations of cadmium mobility and bioavailability in waterlogged paddy soil - Mingming Tao; Xianlin Ke; Jingnan Ma; Linlin Liu; Yanhua Qiu; Zhengyi Hu; Fulai Liu (Journal of Hazardous Materials, 2025)

Cobalt-doped covalent organic framework effectively enhances Fenton-like activity: radical and non-radical dual pathways enhancement - Yunchao Ma; Chuanxue You; Yuxin Yao; Shengnan Qi; Tianyu Zhou; Wei Jiang; Keyu Cui; Bo Hu; Linlin Liu (Chemical Engineering Journal, 2025)

Impacts of spatial resolutions of UAV-LiDAR-derived DEMs on erosion modelling in the hilly and gully Loess Plateau - Wenli Li; Pengfei Li; Lu Yan; Jinfei Hu; Leiqin Wang; Dou Li; Yang Dan; Linlin Huang; Guangju Zhao (CATENA, 2025)

Distribution of glucosinolates and antioxidants in different leaf-layers of Kale (Brassica oleracea var. acephala DC.) - Yafang Luo; Huixia Bai; Linlin Zhao; Qi Hu; Xinyuan Li; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2025)

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

A coupled model of nonlinear dynamical system and deep learning for multi-step ahead daily runoff prediction for data scarce regions - Longxia Qian; Wei Hu; Yong Zhao; Mei Hong; Linlin Fan (Journal of Hydrology, 2025)

One-step synthesis of K3PO4-activated phosphorus-enriched carbons for enhanced carbon capture - Yue Zhi; Yujia Yin; Quji Ciren; Qiang Xiao; Leihong Zhao; Muslum Demir; Utku Bulut Simsek; Xin Hu; Linlin Wang (Journal of Environmental Chemical Engineering, 2025)

Construction of Fenton-like systems based on hierarchical nanoconfinement for efficient antibiotic removal - Linlin Su; Wei Hu; Xiaolun He; Chao Chen; Min Xu; Xiaoyu Yu; Yan Liu; Gang Yang; Lulu Long (Journal of Environmental Chemical Engineering, 2025)

Integration of lipidomics and flavoromics reveals the lipid-flavor transformation mechanism of fish oil from silver carp visceral with different enzymatic hydrolysis - Jinlin Li; Liping Yuan; Linlin Weng; Chengwei Yu; Mingming Hu; Bin Peng; Zongcai Tu (Food Chemistry, 2025)

Quantitative proteomic analysis reveals target proteins of benzyl isothiocyanate against multidrug-resistant Staphylococcus aureus - Xujia Ming; Hongbo Li; Na Li; Zhenbin Liu; Linlin Zhu; Haizhen Mo; Liangbin Hu (Food Bioscience, 2025)

Nitrogen-rich carbon nitride activated peroxymonosulfate for the efficient photodegradation of 2, 4-dichlorophenol: Performance and mechanism insight - Tianyu Zhou; Siyi Wang; Meng Tai; Juan Du; Dongshu Sun; Guangbo Che; Linlin Liu; Chunhong Ma; Bo Hu (Environmental Research, 2025)

Recent progress in visual fire warning and protection materials - Linlin Hu; Ying Xue; Cuihong Sheng; Hailiang Wu; Yijun Yao (Chemical Engineering Journal, 2025)

Optimized Soil Nitrogen Management for Enhanced Photosynthetic Efficiency and Yield in High-Quality Japonica Rice in the Taihu Lake Region - Yunsheng Song; Yulin Xie; Minghui Dong; Fei Chen; Xiuliang Jin; Yajie Hu; Junrong Gu; Peifeng Chen; Yongliang Zhu; Linlin Shi; Yixiao Wang (International Journal of Plant Production, 2025)

Response patterns and community assembly processes of gut microbiota in grass carp subjected to various protein sources and their implications for growth and metabolism - Minglang Cai; Linlin Yang; Lei Zhong; Shouqi Xie; Yi Hu (Fish Physiology and Biochemistry, 2025)

Preparation of M-γAl2O3 (M = Fe, Zn) photocatalyst for the photo-Fenton process: Performance evaluation and mechanistic insights for the efficient degradation of acrylonitrile wastewater - Shen Hu; Hongying Yang; Kejian Diao; Linlin Tong; Zhenan Jin; Dayuan Peng (Journal of Water Process Engineering, 2025)

Impact of freeze-thaw cycles on the structural and quality characteristics of soy protein gels with different 11S/7S protein ratios - Qinlin Hu; Lidan Qiu; Ying Zhu; Yuyang Huang; Linlin Liu; Tianlu Han; YiHan Song; Xiuqing Zhu (Food Chemistry, 2025)

Evaluation of the virulence characteristics of ST11 Salmonella enterica from different sources using a 2D cell model - Linlin Xiao; Yulin Long; Binru Gao; Ying Hu; Tantao Zhang; Qian Xiao; Xiaojie Qin; Xuejuan Xia; Xiang Wang; Zhuosi Li; Qingli Dong (International Journal of Food Microbiology, 2025)

Exploring Boundary Layer Physics and Atmospheric Chemistry in Megacities: Insights from the Beijing 325 m Meteorological Tower - Yele Sun; Zifa Wang; Linlin Wang; Xueling Cheng; Weiqi Xu; Yu Shi; Wei Zhou; Yan Li; Fei Hu; Zhiqiu Gao; Zhongxiang Hong (Advances in Atmospheric Sciences, 2025)

Hydrogen gas enhances Arabidopsis salt tolerance by modulating hydrogen peroxide-mediated redox and ion homeostasis - Linlin Xiao; Yueran Hu; Yiting Wang; Chengsi Lv; Na Zhan; Hongying Duan; Jiuchang Su (Plant Science, 2025)

Sustainable futures for transformational forestry resource-based city: Linking landscape pattern and administrative policy - Linlin Xu; Hu Yu; Linsheng Zhong (Journal of Cleaner Production, 2025)

Physicochemical properties and structure of rice dough and protein based on TGase combined with sodium metabisulfite modification - Xuyang Ren; Wanshan Yang; Huining Zhang; Yang Yu; Xiaofeng Hu; Hongchen Fan; Linlin Liu; Mingshou Lv; Ying Sun; Yanguo Shi; Yanling Hao; Fenglian Chen (Food Chemistry, 2025)

Impact of urban land use and anthropogenic heat on winter and summer outdoor thermal comfort in Beijing - Jiangkang Qian; Linlin Zhang; Uwe Schlink; Xinli Hu; Qingyan Meng; Jianfeng Gao (Urban Climate, 2025)

Multi-perspective evaluation framework of three-dimensional cooling and energy saving potential of urban parks based on numerical simulation - Jianfeng Gao; Linlin Zhang; Qingyan Meng; Xinli Hu; Stephen J. Livesley (Sustainable Cities and Society, 2025)

Characterization and genome analysis of Pseudomonas phages isolated from various sources related to chilled chicken - Haijing Hu; Linlin Cai; Liangting Shao; Xinglian Xu; Huhu Wang; Guanghong Zhou (Food Research International, 2025)

Earthquake-induced Submarine Landslides (EQISLs) and a comparison with their Terrestrial Counterparts: Insights from a New Database - Peng Du; Linlin Li; Achim Kopf; Dawei Wang; Kejie Chen; Huabin Shi; Weitao Wang; Xiaoyi Pan; Gui Hu; Peizhen Zhang (Earth-Science Reviews, 2025)

Salmonella enterica serovar typhimurium effectors spiA and spiC promote replication by modulating iron metabolism and oxidative stress - Keyuan Chen; Jing Wang; Ting Hu; Yiqing Zhao; Yi Wu; Xue Wang; Wei Li; Guiyan Yang; Linlin Zhang; Jiufeng Wang; Yaohong Zhu (Veterinary Microbiology, 2025)

A highly sensitive fluorescent probe based on functionalised ionic liquids for timely detection of trace Hg2+ and CH3Hg+ in food - Siying Che; Yao Fan; Xuemei Hu; Linlin Yin; Haiyan Fu; Yuanbin She (Food Chemistry, 2025)

An Improved Anticipated Learning Machine for Daily Runoff Prediction in Data-Scarce Regions - Wei Hu; Longxia Qian; Mei Hong; Yong Zhao; Linlin Fan (Mathematical Geosciences, 2025)

Comprehensive host cell proteins profiling in biopharmaceuticals by a sensitivity enhanced mass spectrometry strategy using TMT-labeling and signal boosting - Andong Xue; Linlin Kong; Jialin Li; Yuxin Jiao; Zhishang Hu; Bin Fu; Guibin Wang; Wanjun Zhang; Jianheng Li; Weijie Qin (Analytica Chimica Acta, 2025)

Feasibility evaluation of cottonseed protein concentrate to replace soybean meal in the diet of juvenile grass carp (Ctenopharyngodon idellus): Growth performance, antioxidant capacity, intestinal health and microflora composition - Linlin Yang; Minglang Cai; Lei Zhong; Shouqi Xie; Yi Hu; Junzhi Zhang (Aquaculture, 2024)

NIR spectroscopy for quality assessment and shelf-life prediction of kiwifruit - Hongbo Li; Linlin Zhu; Na Li; Zhenbin Liu; Liheng Wang; Bimal Chitrakar; Dan Xu; Zhenkun Cui; Yanhua Tang; Liangbin Hu; Haizhen Mo (Postharvest Biology and Technology, 2024)

Effects of nitrogen fertilization on nitrogen metabolism and grain protein in premium-tasty japonica rice - Yunsheng Song; Minghui Dong; Yajie Hu; Linlin Shi; Junrong Gu; Yuxuan Wang; Shikun Wang; Penghui Cao; Yajie Yu; Yongliang Zhu; Yulin Xie; Zhongying Qiao; et al. (Cereal Research Communications, 2024)

Biocontrol potential of plant growth-promoting rhizobacteria against plant disease and insect pest - Qinhao Jian; Tongrui Zhang; Yingying Wang; Li Guan; Linlin Li; Longna Wu; Shiyan Chen; Yumei He; Hong Huang; Shugang Tian; Hu Tang; Litang Lu (Antonie van Leeuwenhoek, 2024)

Evaluation of soybean meal replacement by Clostridium autoethanogenum protein in diets for juvenile grass carp (Ctenopharyngodon idellus) - Linlin Yang; Minglang Cai; Shouqi Xie; Yi Hu; Junzhi Zhang (Aquaculture, 2024)

Molecular epidemiological investigation of Salmonella isolated from the environment, animals, foods and patients in China - Linlin Xiao; Xiaojie Qin; Hu Xiao; Yuehua Gao; Tanmei Sun; Xiaolu Dong; Yulin Long; Xuejuan Xia; Zhuosi Li; Xiang Wang; Qingli Dong (Food Research International, 2024)

Construction of covalent electrode/solid electrolyte interface for stable flexible solid-state lithium batteries - Junlong Zou; Linlin Wang; Jun Zhang; Qiyue Sun; Yongyin Wang; Mingtao Zheng; Yong Xiao; Hang Hu; Yingliang Liu; Yeru Liang (Chemical Engineering Journal, 2024)

A metal-quercetin-histidine co-coordinated nanoparticle enhances cancer photothermal therapy via reshaping immunosuppressive tumor microenvironment - Shaobo Wang; Shuncheng Yao; Quanhong Hu; Zhuo Wang; Yunchao Zhao; Linlin Li (Chemical Engineering Journal, 2024)

Source characteristics of the 2006 Pingtung earthquake doublet off southern Taiwan and the possible contribution of submarine landslides to the Tsunami - Gui Hu; Linlin Li; Kenji Satake; Tso-Ren Wu; Peitao Wang; D.J. Doong; Philip L.-F. Liu (Earth and Planetary Science Letters, 2024)

Insight of enriched basalts into the nature and evolution of mantle lithosphere beneath craton margins - Hong-Kun Dai; Jianping Zheng; Qing Xiong; Linlin Hu; Xiang Zhou (Science China Earth Sciences, 2024)

Effect of sodium selenite on the synthesis of glucosinolates and antioxidant capacity in Chinese cabbage (Brassica rapa L.ssp.pekinensis) - Yafang Luo; Shuang Zhao; Huan Wang; Huixia Bai; Qi Hu; Linlin Zhao; Tianyi Ma; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2024)

Daily trunk radial growth patterns in relation to precipitation in orange trees in the dry-hot valley region of Southwest China - Xuehui Wei; Dianyu Chen; Panpan Hou; Xiaotao Hu; Lucheng Qiu; Jingying Zhang; Xingwu Duan; Linlin Zhang; Jing Guo (Journal of Hydrology, 2024)

Quantify the extensive crop damage and grain losses caused by underground coal mining subsidence in eastern China - Wenqi Chen; Wu Xiao; Tingting He; Linlin Ruan; Yanling Zhao; Zhenqi Hu (Journal of Cleaner Production, 2024)

Intelligent multi-colorimetric cellulose acetate/cobalt-based metal-organic framework antibacterial film and its application to pork preservation - Qianlan Tao; Yewen Xiao; Xuan Hu; Huaiting Pang; Feng Xiao; Linlin Li; Minmin Chen; Hualin Wang (Food Packaging and Shelf Life, 2024)

Promoting the systematic utilization of reclaimed asphalt pavement (RAP) through waste asphalt-derived carbon in batteries applications - Danqing Li; Xin He; Hu Fu; Wenqi Tan; Shigang Lu; Linlin Wang; Mei Ding; Chunhui Gao; Chuankun Jia (Chemical Engineering Journal, 2024)

Unraveling the dynamics of bed and breakfast clusters development: A multiscale analysis - Hu Yu; Linlin Xu (Applied Geography, 2024)

Provenance signature and tectono–sedimentary setting of the Permian Shihezi formation (Ordos basin, China): Insights from geochemistry and detrital zircon U–Pb dating - Shuyue Zhu; Lei Liu; Linlin Wang; Zhiwei Wang; Jianling Hu; Jingqi Zhang; Chenggong Zhang; Junxing Zhao; Hongde Chen (Marine and Petroleum Geology, 2024)

Mitigation measures of storm surge inundation at an onshore aquaculture farm - Linlin Wang; Shikun Hu; Jing-Cheng Han; Peng Hu; Xuan Yu (Journal of Hydrology, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Energetics of eddy-mean flow interactions in the western tropical Pacific Ocean - Yuchao Hui; Linlin Zhang; Xiaomei Yan; Mengmeng Li; Fan Wang; Dunxin Hu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

An end-capping strategy for shape memory phthalonitrile resins via annealing enables conductivity and wave-absorption - Rongxiang Hu; Fenghua Zhang; Lan Luo; Linlin Wang; Yanju Liu; Jinsong Leng (Chemical Engineering Journal, 2024)

Effects of Nitrogen Fertilizer Reduction Combined with Foliar Fertilizer Application on the Physiological Characteristics and Yield of High-Quality Japonica Rice - Yunsheng Song; Minghui Dong; Fei Chen; Yajie Hu; Yongliang Zhu; Junrong Gu; Peifeng Chen; Yulin Xie; Caiyong Yuan; Zhongying Qiao; Yajie Yu; Penghui Cao; et al. (International Journal of Plant Production, 2024)

Towards robust classification of multi-view remote sensing images with partial data availability - Maofan Zhao; Qingyan Meng; Lifeng Wang; Linlin Zhang; Xinli Hu; Wenxu Shi (Remote Sensing of Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

CO2 methanation reaction over La-modified NiAl catalysts derived from hydrotalcite-like precursors - Linlin Zhou; Xiaoming Guo; Xu Hu; Yaxin Zhang; Jinglin Cheng; Qiangsheng Guo (Fuel, 2024)

Medium optimization and dust suppression performance analysis of microbial-based dust suppressant compound by response surface curve method - Xiangming Hu; Zhiyuan Yang; Yanyun Zhao; Yue Dong; Chengcheng Wang; Linlin Zhang; Yiyun Yu; Kai Wu; Liyan Ren (Environmental Science and Pollution Research, 2024)

Coupled cooling effects between urban parks and surrounding building morphologies based on the microclimate evaluation framework integrating remote sensing data - Qingyan Meng; Jianfeng Gao; Linlin Zhang; Xinli Hu; Jiangkang Qian; Tamás Jancsó (Sustainable Cities and Society, 2024)

Subsurface eddies east of the Philippines: Geographic characteristics, vertical structures, volume and thermohaline transport - Linlin Zhang; Weiqi Song; Yuchao Hui; Zhenxiao Wang; Dunxin Hu (Progress in Oceanography, 2024)

Multipath diffusion process and spatial accumulation simulation of Cd in lead-zinc mining areas - Linlin Li; Bo Wu; Shuhai Guo; Enzhu Hu; Yunlong Zhang; Lixia Sun; Shuqi Li (Journal of Hazardous Materials, 2024)

Deterioration of single-use biodegradable plastics in high-humidity air and freshwaters over one year: Significant disparities in surface physicochemical characteristics and degradation rates - Lingling Hu; Linlin He; Li Cai; Yumeng Wang; Gang Wu; Daoyong Zhang; Xiangliang Pan; Yu-Zhong Wang (Journal of Hazardous Materials, 2024)

Influence of polysaccharide-based co-encapsulants on efficiency, stability, and release of vitamins B12 and D3 in multilayered microcapsules - Linlin He; Shihong Hu; Gang Zhang; Xiao Wang; Yanna Zhao; Qingpeng Wang; Min Liu; Zhengping Wang; Prakash Sangeeta; Zhuang Ding (Journal of Food Engineering, 2024)

A prospective comparative study on bladder volume measurement with portable ultrasound scanner and CT simulator in pelvic tumor radiotherapy - Fei Bai; Qiuxia Hu; Xiaowei Yao; Ming Cheng; Lina Zhao; Linlin Xu (Physical and Engineering Sciences in Medicine, 2024)
Objective: The consistency of bladder volume is very important in pelvic tumor radiotherapy, and portable bladder scanner is a promising device to measure bladder volume. The purpose of this study was to investigate whether the bladder volume of patients with pelvic tumor treated with radiotherapy can be accurately measured using the Meike Palm Bladder Scanner PBSV3.2 manufactured in China and the accuracy of its measurement under different influencing factors. Methods: A total of 165 patients with pelvic tumor undergoing radiotherapy were prospectively collected. The bladder volume was measured with PBSV3.2 before simulated localization. CT simulated localization was performed when the bladder volume was 200-400ml. The bladder volume was measured with PBSV3.2 immediately after localization and recorded. The bladder volume was then delineated on CT simulation images and recorded. To compare the consistency of CT simulation bladder volume and bladder volume measured by PBSV3.2. To investigate the accuracy of PBSV3.2 in different sex, age, treatment purpose, and bladder volume. Results: There was a significant positive correlation with bladder volume on CT and PBSV3.2 ( r = 0.874; p < 0.001). The mean difference between CT measured values and PBSV3.2 was (-0.14 ± 50.17) ml. The results of the different variables showed that the overall mean of PBSV3.2 and CT measurements were statistically different in the age ≥ 65 years, bladder volumes > 400ml and ≤ 400ml groups ( p = 0.028, 0.002, 0.001). There was no statistical significance between the remaining variables. The volume difference between PBSV3.2 measurement and CT was 12.87ml in male patients, which was larger than that in female patients 3.27ml. Pearson correlation analysis showed that the correlation coefficient was 0.473 for bladder volume greater than 400ml and 0.868 for bladder volume less than 400ml; the correlation coefficient of the other variables ranged from 0.802 to 0.893. Conclusion: This is the first large-sample study to evaluate the accuracy of PBSV3.2 in a pelvic tumor radiotherapy population using the convenient bladder scanner PBSV3.2 made in China. PBSV3.2 provides an acceptable indicator for monitoring bladder volume in patients with pelvic radiotherapy. It is recommended to monitor bladder volume with PBSV3.2 when the planned bladder volume is 200-400ml. For male and patients ≥ 65 years old, at least two repeat measurements are required when using a bladder scanner and the volume should be corrected by using a modified feature to improve bladder volume consistency.

Multi-sensor integrated mapping of global XCO2 from 2015 to 2021 with a local random forest model - Jiabin Chen; Ruohua Hu; Leyan Chen; Zihao Liao; Linlin Che; Tongwen Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Vertical distribution of intraseasonal variation signals in the Kuroshio Current source area during 2018–2020 - Haobo Gong; Fujun Wang; Feng Liu; Linlin Zhang; Dunxin Hu (Frontiers in Marine Science, 2024)
In the Kuroshio Current (KC) source area, intraseasonal variation (ISV) plays a significant role in dynamic oceanic processes. This study used data collected from three moorings (122.7°E, 123°E, 123.3°E) along 18°N from January 2018 to May 2020 to investigate the ISVs of meridional velocities. Notably, our findings reveal that the ISV above 200 m has a period of approximately 56 days and its intensity exhibits a gradual increase toward the west. For the 500–800 m depth interval, the ISV period is 73 days at 122.7°E/18°N and 60 days at 123.3°E/18°N. This discrepancy indicates that the ISVs have different vertical structures and frequencies at 122.7°E and 123.3°E along 18°N. In particular, at 122.7°E/18°N, the distinctiveness of two different periods of ISVs in surface and subsurface layers was more pronounced in 2018 than in 2019. The analyses of eddy kinetic energy distribution and eddy tracking indicate a connection between ISV in stratification and locally generated mesoscale eddies in the KC source area. Specifically, the stronger eddy activity in 2018, in contrast with that in 2019, correlates with a more pronounced ISV. Energy analysis demonstrates a distinct positivity in the baroclinic conversion rate (BC) in the surface layer (upper 200 m) of the KC source region, surpassing the absolute value of the barotropic conversion rate (BT). This finding indicates a notable shift of energy from eddy available potential energy to eddy kinetic energy, strengthening the high-frequency ISV signals in this area. In the subsurface layer, a strong negative BT is observed west of 122.8°E, with its absolute value exceeding the BC. This finding indicates that the energy is converted from eddy kinetic energy into mean kinetic energy, resulting in the appearance of the Luzon Undercurrent (LUC) at mooring station 122.7°E/18°N, characterized by a low frequency of ISV. Contrastingly, a positive BT plays a dominant role at 123.3°E/18°N, leading to the disappearance of the LUC amid an apparent presence of high-frequency ISV.

Sulfur-Doped porous carbon Adsorbent: A promising solution for effective and selective CO2 capture - Jiali Bai; Jiawei Shao; Qiyun Yu; Muslum Demir; Bilge Nazli Altay; Turgunov Muhammad Ali; Yongfu Jiang; Linlin Wang; Xin Hu (Chemical Engineering Journal, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Hippocampal subfield volumes in mild cognitive impairment and alzheimer’s disease: a systematic review and meta-analysis - Jinhuan Zhang; Linlin Xie; Changjiang Cheng; Yongfeng Liu; Xiaodong Zhang; Haoyu Wang; Jingting Hu; Haibo Yu; Jinping Xu (Brain Imaging and Behavior, 2023)

Establishment of ultrasensitive immunoassay strip based on colloidal gold-McAb probe for detecting cyproheptadine hydrochloride and six phenothiazines in feed - Xiaofei Hu; Guanqiong Na; Yaning Sun; Yunrui Xing; Linlin Chen; Zhang Gaiping (Food Additives & Contaminants: Part A, 2023)

Depth investigation of the regulation mechanism of SiO2 on the denitrification performance and sulfur resistance of MnCe/Ti SCR catalyst - Mengxia Qing; Linlin Zhang; Liang Liu; Yaxin Chen; Yunda Su; Sheng Su; Song Hu; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2023)

Novel bio-degradation shortcut for the treatment of acrylonitrile-containing wastewater using column bio-oxidation with Sulfurovum bacteria in activated sludge - Shen Hu; Hongying Yang; Kejian Diao; Linlin Tong; Zhenan Jin; Dayuan Peng; Huiqun Niu (Journal of Water Process Engineering, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Li-intercalation chemistry of few-layer borophene with ultrahigh capacity and fast kinetics - Linlin Guo; Huili Wang; Zhonghan Wu; Xinru Yang; Ruoxuan Ma; Yanfang Hu; Geng Li; Dongjie Shi; Wei Xie; Wei Zhang; Fujun Lan; Limin Zhou; et al. (Chemical Engineering Journal, 2023)

Gas-pressurized torrefaction of lignocellulosic solid wastes: Low-temperature deoxygenation and chemical structure evolution mechanisms - Liu Shi; Zhenzhong Hu; Xian Li; Shuo Li; Linlin Yi; Xiaohua Wang; Hongyun Hu; Guangqian Luo; Hong Yao (Bioresource Technology, 2023)

A uniform methodology of local cooling and warming effects for different urban site types: multi-perspective assessment based on four northern Chinese cities - Jianfeng Gao; Qingyan Meng; Die Hu; Linlin Zhang; Xinli Hu; Jiangkang Qian (Sustainable Cities and Society, 2023)

Characteristics of anthropogenic heat with different modeling ideas and its driving effect on urban heat islands in seven typical Chinese cities - Jiangkang Qian; Qingyan Meng; Linlin Zhang; Uwe Schlink; Xinli Hu; Jianfeng Gao (Science of The Total Environment, 2023)

Anthropogenic heat variation during the COVID-19 pandemic control measures in four Chinese megacities - Qingyan Meng; Jiangkang Qian; Uwe Schlink; Linlin Zhang; Xinli Hu; Jianfeng Gao; Qiao Wang (Remote Sensing of Environment, 2023)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Evolution of the landscape pattern in the Xin'an River Basin and its response to tourism activities - Linlin Xu; Hu Yu; Linsheng Zhong (Science of The Total Environment, 2023)

Manipulating electron redistribution induced by asymmetric coordination for electrocatalytic water oxidation at a high current density - Sheng Zhao; Feng Hu; Lijie Yin; Linlin Li; Shengjie Peng (Science Bulletin, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

In vitro gastrointestinal digestion of whole grain noodles supplemented with soluble dietary fiber and their effects on children fecal microbiota - Linlin Gao; Lin Zhang; Huan Liu; Jielun Hu (Food Bioscience, 2023)

Efficient and selective removal of Hg(II) from water using recyclable hierarchical MoS2/Fe3O4 nanocomposites - Shiyu Li; Lin Yang; Jialong Wu; Linlin Yao; Deming Han; Yong Liang; Yongguang Yin; Ligang Hu; Jianbo Shi; Guibin Jiang (Water Research, 2023)

Self-powered energy harvesting and implantable storage system based on hydrogel-enabled all-solid-state supercapacitor and triboelectric nanogenerator - Zhuo Wang; Shuncheng Yao; Shaobo Wang; Zhirong Liu; Xingyi Wan; Quanhong Hu; Yunchao Zhao; Cheng Xiong; Linlin Li (Chemical Engineering Journal, 2023)

Simultaneous oxidation and absorption of nitric oxide and sulfur dioxide by peroxymonosulfate activated by bimetallic metal-organic frameworks - Zhaoxin Wan; Xiude Hu; Chengbo Li; Jiawei Zhang; Qi Wang; Long Fang; Linlin Zhang; Qingjie Guo; Deshuai Sun (Journal of Environmental Chemical Engineering, 2023)

Global, regional, and national deaths, disability-adjusted life years, years lived with disability, and years of life lost for the global disease burden attributable to second-hand smoke, 1990–2019: A systematic analysis for the Global Burden of Disease Study - Chunxia Zhai; Dingtao Hu; Guanghui Yu; Wanqin Hu; Qiqun Zong; Ziye Yan; Yuhua Wang; Linlin Wang; Tingyu Zhang; Hongyu Sun; Ling Cai; Liangyu Cui; et al. (Science of The Total Environment, 2023)

Nitrogen-doped porous carbons from polyacrylonitrile fiber as effective CO2 adsorbents - Changdan Ma; Jiali Bai; Xin Hu; Zhuohan Jiang; Linlin Wang (Journal of Environmental Sciences, 2023)

Impact of diurnal temperature range on other infectious diarrhea in Tongcheng, China, 2010–2019: a distributed lag non-linear analysis - Linlin Wang; Jian Cheng; Guanghui Yu; Qiqun Zong; Chunxia Zhai; Wanqin Hu; Yuhua Wang; Ziye Yan; Tingyu Zhang; Junwu Wang; Chengye Zhang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Contribution of the TGFβ signaling pathway to pigmentation in sea cucumber (Apostichopus japonicus) - Linlin Yao; Bin Zhao; Qi Wang; Xuyang Jiang; Sha Han; Wei Hu; Chenglin Li (Frontiers in Marine Science, 2023)
Pigmentation mediated by the transforming growth factor β (TGFβ) signaling pathway is a key trait for understanding environmental adaptability and species stability. In this study, TGFβ signaling pathway members and their expression patterns in different color morphs of the sea cucumber Apostichopus japonicus were evaluated. Using a bioinformatics approach, 22 protein sequences of TGFβ signaling pathway members in A. japonicus were classified, including 14 that were identified for the first time in the species, including 7 ligands, 6 receptors, and 1 R-Smad. We further evaluated mRNA expression data for different color morphs and pigmentation periods. These results support the hypothesis that both subfamilies of the TGFβ superfamily, i.e., the TGFβ/activin/Nodal and BMP/GDF/AMH subfamilies, are involved in the regulation of pigmentation in A. japonicus . The former subfamily was complete and contributes to the different color morphs. The BMP/GDF/AMH subfamily was incomplete. BMP2/4-induced differentiation of white adipocytes was regulated by the BMP2/4–ACVR2A–Smad1 signaling pathway. These findings provide insight into the TGFβ family in early chordate evolution as well as the molecular basis of color variation in an economically valuable species.

Air pollution exposure and ovarian reserve impairment in Shandong province, China: The effects of particulate matter size and exposure window - Lihong Pang; Wenhao Yu; Jiale Lv; Yunde Dou; Han Zhao; Shanshan Li; Yuming Guo; Gongbo Chen; Linlin Cui; Jingmei Hu; Yueran Zhao; Qi Zhao; et al. (Environmental Research, 2023)

Convolutional neural networks (CNNs)-based multi-category damage detection and recognition of high-speed rail (HSR) reinforced concrete (RC) bridges using test images - Lingkun Chen; Wenxin Chen; Lu Wang; Chencheng Zhai; Xiaolun Hu; Linlin Sun; Yuan Tian; Xiaoming Huang; Lizhong Jiang (Engineering Structures, 2023)

Cenozoic plants from Tibet: An extraordinary decade of discovery, understanding and implications - Zhekun Zhou; Jia Liu; Linlin Chen; Robert A. Spicer; Shufeng Li; Jian Huang; Shitao Zhang; Yongjiang Huang; Linbo Jia; Jinjin Hu; Tao Su (Science China Earth Sciences, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Synergistic relationship or not? Understanding the resilience and efficiency of the tourism economy: evidence from Hainan Province, China - Pengfei Zhang; Hu Yu; Linlin Xu; Wei Guo; Mingzhe Shen (Environment, Development and Sustainability, 2023)

Flexible and highly piezoelectric nanofibers with organic–inorganic coaxial structure for self-powered physiological multimodal sensing - Xingyi Wan; Zhuo Wang; Xinyang Zhao; Quanhong Hu; Zhou Li; Zhong Lin Wang; Linlin Li (Chemical Engineering Journal, 2023)

Combining microclimatic monitoring with questionnaires, for understanding thermal comfort in Linpan, a typical agricultural ecosystem settlement in the Chengdu plain - Linlin Chen; Gretchen Kalonji; Lilai Xu; Pufan Ma; Linmiao Hu (Building and Environment, 2023)

Seasonal variability of the North Equatorial Current–Kuroshio Current–Mindanao Current based on observations - Fujun Wang; Linlin Zhang; Junqiao Feng; Dunxin Hu (Frontiers in Marine Science, 2022)
Utilizing the direct mooring observation along 130°E (10.5°N, 13°N, 15.5°N, and 18°N), 18°N (122.7°E, 123°E, and 123.3°E), and 8°N (127°E) and satellite data, the seasonal variabilities of the North Equatorial Current (NEC), Kuroshio Current (KC), and Mindanao Current (MC) were investigated. The southern part of the NEC along 130°E, the KC along 18°N, and the MC along 8°N featured similar seasonal cycles: that is, the currents were strong in spring and weak in autumn, while the KC along 18°N featured another peak in winter. Moreover, the seasonal phase of the NEC along 130°E was latitude-dependent; it advanced slightly from 10°N to 14°N and delayed poleward. The seasonal variabilities of the three currents were mainly controlled by local winds and Rossby waves via a geostrophic relationship, as the mooring observation was consistent with satellite data. The calculation shows that the local wind was dominant in the above mentioned in-phase areas (i.e., the southern part of the NEC, KC, and MC), while Rossby waves played an important role in the northern part of the NEC. The results indicate that the NEC–KC–MC system had the same zonal dynamics but different meridional dynamics across seasons.

Incorporating egg-transporting pathways into conservation plans of spawning areas: An example of small yellow croaker (Larimichthys polyactis) in the East China Sea zone - Zunlei Liu; Yan Jin; Linlin Yang; Liping Yan; Yi Zhang; Min Xu; Jianhua Tang; Yongdong Zhou; Fen Hu; Jiahua Cheng (Frontiers in Marine Science, 2022)
Backward-in-time Lagrangian model can identify potential spawning areas by reconstructing egg drift trajectories, contributing to accurately designing potential priority conservation plans for spawning areas. In this study, we apply this approach to investigate the small yellow croaker ( Larimichthys polyactis ) with commercial value in China. A two-step spatial random forest (RF) model is used to predict the occurrence probability and abundance of their eggs and describe the optimal ecological range of environmental factors. A priority protection index (BPPI) of the spawning areas is established by combining the sites with the optimal occurrence and abundance and integrating backward tracking pathways. The result indicates that the model with 1-2 day time lags of environmental variables shows the optimum explanatory power. Temperature and salinity are the most important factors affecting oogenesis and show a regime shift in the response curve. They reflect the physiological regulation of parental sexual maturation by the environment. In addition, egg abundance correlates more strongly with chlorophyll-a (Chl a) concentration and depth, suggesting that parents prefer environments with shallow water and high prey density for spawning activities. The egg retrieval shows that the potential spawning sources are distributed near the southeastern part of the oogenesis site, with a maximum egg dispersal distance of no more than 30 km. This finding confirms that the coastal regions of Jiangsu Province are an important spawning ground for the small yellow croaker, making a significant contribution to the productivity and resilience of the fish.

Interannual variations of the North Equatorial Current/Undercurrent from mooring array observations - Ying Huang; Linlin Zhang; Fujun Wang; Fan Wang; Dunxin Hu (Frontiers in Marine Science, 2022)
Interannual variability of the North Equatorial Current (NEC)/Undercurrent (NEUC) in the northwestern Pacific was investigated with the mooring array measurements at 130°E during 2014-2021, in combination with the satellite altimetry. Mooring observations indicate that the velocity of the NEC/NEUC in the upper 900 m exhibits significant variations on the interannual time scale. The westward-flowing NEC strengthens when the underlying eastward-flowing NEUC weakens, and the NEUC branch at 8.5°N is intensified during the mature phase of El Niño and reaches the maximum velocity during the decay phase of El Niño. The phase of the interannual variation of the currents delays with the increasing latitude, with the signal at 15°N lagging that at 8.5°N by about one year. Based on a 1.5 layer reduced gravity model, the interannual variation is suggested to be controlled mainly by the westward propagating baroclinic Rossby wave induced by the wind stress curl forcing in the central Pacific. Different propagating speed of the baroclinic Rossby wave at different latitudes explains the meridional phase lag of the interannual signal. Empirical Orthogonal Function and vertical mode decomposition analysis suggest that the interannual variation of the NEC/NEUC velocity in the northern part is dominated by surface-intensified signals with a vertical structure of the first baroclinic mode, while that in the southern part is dominated by subsurface-intensified signals which is associated with the combination of the first two baroclinic modes. The low-order mode baroclinic response of the ocean to the wind forcing accounts for the interannual fluctuation of the NEC/NEUC velocity observed by the mooring array.

The near-inertial waves observed east of the Philippines - Shengming Yuan; Xiaomei Yan; Linlin Zhang; Bing Yang; Chongguang Pang; Dunxin Hu (Journal of Oceanology and Limnology, 2022)

Two Flavors of Intraseasonal Variability and Their Dynamics in the North Equatorial Current/Undercurrent Region - Zhenxiao Wang; Linlin Zhang; Yuchao Hui; Fan Wang; Dunxin Hu (Frontiers in Marine Science, 2022)
Significant surface-intensified and subsurface-intensified intraseasonal variability (ISV) of the North Equatorial Current/Undercurrent with different periods are detected to coexist with mooring ADCP measurements at 13°N, 130°E. The ISV of the currents in the upper 200 m has a relatively shorter period of 45 days, while the period of the subsurface-intensified ISV between 400 and 800 m is around 85 days. By combining with sea surface height measurements from satellite altimeters and outputs from an eddy-resolving ocean general circulation model, the origin and dynamic mechanism of the two flavors of ISV are investigated. Eddy trajectory tracking and energy analysis indicate that both the surface-intensified and subsurface-intensified ISV are related to locally generated meso-scale eddies near the mooring sites. Stability analysis suggests the surface-intensified ISV is related to the baroclinic instability induced by the vertical velocity shear of the North Equatorial Current. While the generation of the subsurface-intensified ISV is more complex and is partly related to the enhanced barotropic instability induced by the intensified horizontal shear of the subsurface zonal background flow.

Colloidal gold-based immunochromatographic strip assay for the rapid detection of diminazene in milk - Linlin Chen; Yaning Sun; Xiaofei Hu; Yunrui Xing; Sharon Kwee; Guanqiong Na; Gaiping Zhang (Food Additives & Contaminants: Part A, 2020)

Instability in boundary layer between the North Equatorial Current and underlying zonal jets based on mooring observations - Fujun Wang; Junqiao Feng; Qingye Wang; Linlin Zhang; Shijian Hu; Dunxin Hu (Journal of Oceanology and Limnology, 2020)

DNA Methylation Analysis of the NR3C1 Gene in Patients with Schizophrenia - Linlin Liu; Jian Wu; Lili Qing; Jiajue Li; Hao Yang; Aicen Ji; Ming Yan; Liping Hu; Shengjie Nie (Journal of Molecular Neuroscience, 2020)

Review on observational studies of western tropical Pacific Ocean circulation and climate - Dunxin Hu; Fan Wang; Janet Sprintall; Lixin Wu; Stephen Riser; Sophie Cravatte; Arnold Gordon; Linlin Zhang; Dake Chen; Hui Zhou; Kentaro Ando; Jianing Wang; et al. (Journal of Oceanology and Limnology, 2020)

Dynamic features of near-inertial oscillations in the Northwestern Pacific derived from mooring observations from 2015 to 2018 - Shijian Hu; Lingling Liu; Cong Guan; Linlin Zhang; Jianing Wang; Qingye Wang; Jie Ma; Fujun Wang; Fan Jia; Junqiao Feng; Xi Lu; Fan Wang; et al. (Journal of Oceanology and Limnology, 2020)

Comparison of different soil dielectric models for microwave soil moisture retrievals - Linlin Zhang; Qingyan Meng; Die Hu; Ying Zhang; Shun Yao; Xu Chen (International Journal of Remote Sensing, 2020)

Gelatin Methacrylate (GelMA)-Based Hydrogels for Cell Transplantation: an Effective Strategy for Tissue Engineering - Shining Xiao; Tengfei Zhao; Jingkai Wang; Chenggui Wang; Jiangnan Du; Liwei Ying; Jiangtao Lin; Caihua Zhang; Wanglu Hu; Linlin Wang; Kan Xu (Stem Cell Reviews and Reports, 2019)

Spatiotemporal evolution of C3/C4 vegetation and its controlling factors in southern China since the last glacial maximum - Linlin Cui; Jianfang Hu; Xu Wang (Science China Earth Sciences, 2019)

Tissue Distribution and Gender-Specific Protein Expression of Cytochrome P450 in five Mouse Genotypes with a Background of FVB - Jiamei M. Chen; Qisong S. Zhang; Xiaoyan Y. Li; Xia Gong; Yanjiao J. Ruan; Sijing J. Zeng; Linlin L. Lu; Xiaoxiao X. Qi; Ying Wang; Ming Hu; Lijun J. Zhu; Zhongqiu Q. Liu (Pharmaceutical Research, 2018)

The role of Ustilaginoidea virens sclerotia in increasing incidence of rice false smut disease in the subtropical zone in China - Mingli Yong; Qide Deng; Linlin Fan; Jiankun Miao; Chaohui Lai; Hongming Chen; Xiujuan Yang; Shu Wang; Furu Chen; Li Jin; Binghui Yang; Yuanjun Bai; et al. (European Journal of Plant Pathology, 2018)

MicroRNA-192 regulates hypertrophic scar fibrosis by targeting SIP1 - Yan Li; Julei Zhang; Wei Zhang; Yang Liu; Yuehua Li; Kejia Wang; Yijie Zhang; Chen Yang; Xiaoqiang Li; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

The vertical structure and variability of the western boundary currents east of the Philippines: case study from in situ observations from December 2010 to August 2014 - Fujun Wang; Linlin Zhang; Dunxin Hu; Qingye Wang; Fangguo Zhai; Shijian Hu (Journal of Oceanography, 2017)

Assessing the wavelength-dependent ability of solar-induced chlorophyll fluorescence to estimate the GPP of winter wheat at the canopy level - Liangyun Liu; Xinjie Liu; Jiaochan Hu; Linlin Guan (International Journal of Remote Sensing, 2017)

Disposition of Flavonoids for Personal Intake - Shuqiang Liu; Haihui Zheng; Rongjin Sun; Huangyu Jiang; Jiamei Chen; Jia Yu; Qisong Zhang; Qingwei Chen; Lijun Zhu; Ming Hu; Linlin Lu; Zhongqiu Liu (Current Pharmacology Reports, 2017)

miR-155 promotes cutaneous wound healing through enhanced keratinocytes migration by MMP-2 - Longlong Yang; Zhao Zheng; Qin Zhou; Xiaozhi Bai; Lei Fan; Chen Yang; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Exosomes derived from human amniotic epithelial cells accelerate wound healing and inhibit scar formation - Bin Zhao; Yijie Zhang; Shichao Han; Wei Zhang; Qin Zhou; Hao Guan; Jiaqi Liu; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Gelatin microspheres containing calcitonin gene-related peptide or substance P repair bone defects in osteoporotic rabbits - Jianghao Chen; Wei Liu; Jinxiu Zhao; Cong Sun; Jie Chen; Kaijin Hu; Linlin Zhang; Yuxiang Ding (Biotechnology Letters, 2017)

Estimate of Boundary-Layer Depth Over Beijing, China, Using Doppler Lidar Data During SURF-2015 - Meng Huang; Zhiqiu Gao; Shiguang Miao; Fei Chen; Margaret A. LeMone; Ju Li; Fei Hu; Linlin Wang (Boundary-Layer Meteorology, 2017)

Trivalent chromium alleviates oleic acid induced steatosis in SMMC-7721 cells by decreasing fatty acid uptake and triglyceride synthesis - Song Wang; Jian Wang; Xiaonan Zhang; Linlin Hu; Zhijia Fang; Zhiwei Huang; Ping Shi (BioMetals, 2016)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

Variability of Antarctic Intermediate Water south of Australia and its relationship with frontal waves - LinLin Zhang; XiaoMei Yan; Che Sun; DunXin Hu (Science China Earth Sciences, 2016)

Allogeneic adipose-derived stem cells promote survival of fat grafts in immunocompetent diabetic rats - Jun Zhang; Xiaozhi Bai; Bin Zhao; Yunchuan Wang; Linlin Su; Peng Chang; Xujie Wang; Shichao Han; Jianxin Gao; Xiaolong Hu; Dahai Hu; Xiaoyan Liu (Cell and Tissue Research, 2016)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

MRP1 knockdown down-regulates the deposition of collagen and leads to a reduced hypertrophic scar fibrosis - Yan Li; Longlong Yang; Zhao Zheng; Jihong Shi; Xue Wu; Hao Guan; Yanhui Jia; Ke Tao; Hongtao Wang; Shichao Han; Jianxin Gao; Bin Zhao; et al. (Journal of Molecular Histology, 2015)

Triple Recycling Processes Impact Systemic and Local Bioavailability of Orally Administered Flavonoids - Peimin Dai; Lijun Zhu; Feifei Luo; Linlin Lu; Qiang Li; Liping Wang; Ying Wang; Xinchun Wang; Ming Hu; Zhongqiu Liu (The AAPS Journal, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

A comparison of de-noising methods for differential phase shift and associated rainfall estimation - Zhiqun Hu; Liping Liu; Linlin Wu; Qing Wei (Journal of Meteorological Research, 2015)

Genetic manipulation of a high-affinity PHR1 target cis-element to improve phosphorous uptake in Oryza sativa L. - Wenyuan Ruan; Meina Guo; Linlin Cai; Hongtao Hu; Changying Li; Yu Liu; Zhongchang Wu; Chuanzao Mao; Keke Yi; Ping Wu; Xiaorong Mo (Plant Molecular Biology, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Mesoaccumbens dopamine signaling alteration underlies behavioral transition from tolerance to sensitization to morphine rewarding properties during morphine withdrawal - Linlin Sun; Ling Hu; Yijing Li; Cailian Cui (Brain Structure and Function, 2014)

Transcriptomic analysis reveals key regulators of mammogenesis and the pregnancy-lactation cycle - YuanYuan Zhou; Wei Gong; JingFa Xiao; JiaYan Wu; LinLin Pan; XiaoNuan Li; XuMin Wang; WeiWei Wang; SongNian Hu; Jun Yu (Science China Life Sciences, 2014)

Transcriptome profiling of the developing postnatal mouse testis using next-generation sequencing - Wei Gong; LinLin Pan; Qiang Lin; YuanYuan Zhou; ChengQi Xin; XiaoMin Yu; Peng Cui; SongNian Hu; Jun Yu (Science China Life Sciences, 2013)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Identification and genomic analysis of two duck-origin Tembusu virus strains in southern China - Linlin Li; Hejia An; Minhua Sun; Jiawen Dong; Jianfeng Yuan; Qilin Hu (Virus Genes, 2012)

High-throughput sequencing-based gene profiling on multi-staged fruit development of date palm (Phoenix dactylifera, L.) - Yuxin Yin; Xiaowei Zhang; Yongjun Fang; Linlin Pan; Gaoyuan Sun; Chengqi Xin; Mohammed M. Ba Abdullah; Xiaoguang Yu; Songnian Hu; Ibrahim S. Al-Mssallem; Jun Yu (Plant Molecular Biology, 2012)

A ras GTPase-activating protein-binding protein, TaG3BP, associated with the modulation of male fertility in a thermo-sensitive cytoplasmic male sterile wheat line - Linlin Zhou; Guoqi Song; Beiru He; Yin-Gang Hu (Molecular Genetics and Genomics, 2011)

Effects of Aluminum Exposure on Serum Sex Hormones and Androgen Receptor Expression in Male Rats - Hao Sun; Chongwei Hu; Linlin Jia; Yanzhu Zhu; Hansong Zhao; Bing Shao; Nan Wang; Zhigang Zhang; Yanfei Li (Biological Trace Element Research, 2011)

Identification and Analysis of Muscle-Related Protein Isoforms Expressed in the White Muscle of the Mandarin Fish (Siniperca chuatsi) - Guoqiang Zhang; Wuying Chu; Songnian Hu; Tao Meng; Linlin Pan; Renxue Zhou; Zhen Liu; Jianshe Zhang (Marine Biotechnology, 2011)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)

Expression of phytoene synthase gene (Psy) is enhanced during fruit ripening of Cara Cara navel orange (Citrus sinensis Osbeck) - Nengguo Tao; Zhiyong Hu; Qin Liu; Juan Xu; Yunjiang Cheng; Linlin Guo; Wenwu Guo; Xiuxin Deng (Plant Cell Reports, 2007)